Nestmate Recognition in Social Insects: What Does It Mean to Be Chemically Insignificant? - Lorenzi, Maria Cristina; d'Ettorre, Patrizia (Frontiers in Ecology and Evolution, 2020)
Social insects use the blend of hydrocarbons present on their cuticle to efficiently distinguish nestmates from aliens. Intruders must therefore find a strategy to break the recognition code in order to exploit the colony resources. Twenty years ago, the concept of ‘chemical insignificance’ was introduced to characterize those parasites bearing almost no recognition cues on their cuticle, thus appearing chemically undetectable to their hosts. In some cases, intruders do possess cuticular hydrocarbons, but these are present in lower amount with respect to their hosts and/or they belong to different classes than the hydrocarbons typically used as recognition cues. We propose to include these cases under the label of chemical insignificance. If chemical compounds are absent on the cuticle of the intruder, or if they are produced but not perceived by the host (e.g., below the detection threshold), or if they are perceived but not meaningful, in all cases the result is identical: the profile of the intruder appears chemically neutral, thus it is irrelevant for the host. We also discuss the consequences of producing low amounts of cuticular hydrocarbons, given that their original function is to act as a barrier against desiccation. Clarifying the concept of chemical insignificance will help unifying terminology and stimulate interdisciplinary research efforts involving simultaneous investigations of chemical profiles, behavior and physiology to elucidate the proximate and ultimate mechanisms characterizing the co-evolutionary arms race between hosts and parasites.